A comparison study of three-dimensional radiation stress formulations. Issue 2 (3rd April 2019) - Ji, Chao; Zhang, Qinghe; Wu, Yongsheng
ABSTRACT: In the present study, 4 three-dimensional radiation stress formulations are examined using a coupled wave-current model system based on unstructured grids. The formulations include one commonly used formulation and three recently developed formulations. The four formulations are evaluated against the laboratory data by simulating oblique incident waves on a planar beach, normal incident waves on a planar beach, a barred beach and a nearshore barred beach with rip channels. The simulation of longshore currents indicates that the results from the four formulations are similar overall and agree with the measured data. For the vertical distribution of the cross-shore velocities, the M03 and J17 models show relatively good agreement within the surf zone. However, outside of the surf zone, only the J17 model successfully reproduces the vertical flow structure. The M15 and X17 models may produce relatively large errors both inside and outside of the surf zone. Moreover, this study shows that the differences in the circulation results for the four models are primarily due to the vertical radiation stress terms.